Enhanced Oxygen Ion Conductivity in Composite Film Electrolytes with Aligned Nanowires. Issue 13 (26th April 2018) - Zhang, Mengfei; Li, Tianjun; Li, Zheng; Xing, Yan; Zhao, Xiaohui; Shahid, Muhammad; Yuan, Yajie; Nishijima, Hiroki; Pan, Wei
Abstract: Recently, tuning oxygen ionic transport in film through tensile stress has generated much interest. Herein, composite samarium neodymium codoped ceria (SNDC) thin film electrolytes are fabricated with aligned yttria‐stabilized zirconia (YSZ) nanowires to increase the oxygen conductivity by introducing tensile strain. The morphologies and oxygen‐ion conductivities are studied according to the diameter of YSZ nanowires in the composite electrolytes. The composite SNDC film electrolytes with YSZ nanowires exhibit great long‐term chemical stability with excellent conductivity at intermediate temperature, which is more than twice times higher than that of SNDC film. By using Raman spectrum and sin 2 ψ‐methodology, it is found that this conductivity enhancement originates from the bending surface of the film on the nanowires that can produce tensile strain paralleled to the film surface. Abstract : Samarium neodymium co‐doped ceria composite film electrolytes are fabricated herein with aligned YSZ nanowires to increase the oxygen conductivity by creating tensile strain. By using Raman spectrum and sin 2 ψ‐methodology, it is found that this conductivity enhancement originates from the bending surface of the film on the nanowires that can produce tensile strain paralleled to the film surface.